Functionalising AFM tips for pick and place manipulation of micro and nanoparticles - Soh, JHE (2021)
Nanofabrication techniques have always been at the heart of realising novel functional nanodevices. Modern nanomanufacturing relies heavily on lithography, which is the patterning of two-dimensional structures on radiation sensitive polymers in multiple steps to create nanodevices. Although suitable for mass manufacturing, lithography lacks the capability to precisely manipulate a single to few particles. The main goal of my research is to develop new technologies that are capable of manipulating single to few particles ranging from nanometer to micrometer scale. With the development of these new particle manipulation technologies, we demonstrate new applications that would have been difficult to realise with current existing nanomanufacturing methods. Here, we will look at how the atomic force microscope (AFM) can be used as a particle manipulator. The cantilever of the AFM acts as a robotic arm with nanometer precision in all three spatial dimensions. We show that by appropriately functionalising or modifying the cantilever, we can manipulate different types of particles (from nano- to micrometer sized) for various applications.